Taco Bell thanks you for suing them - Crandall, William, 1956- (SAGE knowledge. Cases., 2016)
This case describes Taco Bell's 2011 marketing campaign: 'Thank You for Suing Us'. This well-managed campaign was effective enough that it actually led to the withdrawal of a lawsuit against the fast food chain.